Mineral fibre analysis and routes of exposure to asbestos in the development of mesothelioma in an English region. Issue 1 (1st January 1999) - Howel, D; Gibbs, A; Arblaster, L; Swinburne, L; Schweiger, M; Renvoize, E; Hatton, P; Pooley, F
Abstract : OBJECTIVES: To compare the concentrations of inorganic fibres in the lungs in cases of mesothelioma and controls: to determine whether concentrations of retained asbestos fibres differ with the different exposures identified from interview; and to investigate the existence of a cut off point in concentrations of asbestos fibres that indicates occupational exposure. METHODS: Case-control study; 147 confirmed cases of mesothelioma and 122 controls identified from deaths occurring in four districts of Yorkshire between 1979 and 1991. Surviving relatives were interviewed to determine lifetime exposure history to asbestos. Mineral fibre analysis was carried out on lung tissue from postmortem examinations. RESULTS: Odds on high concentrations of retained asbestos fibres were greater in cases than controls. After excluding subjects with occupational and paraoccupational exposure, the odds on high concentrations were still greater in cases than controls, but only significantly so for amphiboles. There was only a weak relation between probability of occupational exposure to asbestos and concentrations of retained asbestos fibres, and no significant difference in fibre concentrations was found between subjects who had been exposed to asbestos through different routes: these comparisons were only based on small groups. There was considerable overlap in concentrations of retained asbestos fibres between cases and controls with and without histories of occupational exposure. CONCLUSIONS: The study has confirmed previous results of higher concentrations of asbestos fibres in cases than controls, and has shown that this is still found in subjects with little evidence of occupational and para-occupational exposure. The overlap in concentrations of retained asbestos for different groups of subjects did not suggest a clear cut of value.